Smart mobile app for buying and selling pre-loved goods - Chen, Xi (Nanyang Technological University, 2022)
Ecommerce is the buying and selling of goods or services on the Internet. According to eMarketer, in 2022, global retail e-commerce sales will surpass $5 trillion for the first time, accounting for more than a fifth of overall retail sales. Furthermore, by 2025, total spending will exceed $7 trillion, despite slowing growth. In terms of choice of e-commerce platform, compared to traditional website platforms, mobile apps can offer better personalization. Apps can track customer engagement and then utilize it to provide custom recommendations and updates to users. Besides, mobile apps have the advantage of using features of mobile devices like a camera, contact list, GPS, storage, etc. This project is targeted to develop an all-in-one lifestyle platform for buying and selling pre-loved items. It contains a front-end mobile application and a back-end server. They can interact with each other to perform relative functions. The primary function to be achieved is to allow users to publish their second-hand goods and accomplish the purchase. This report elaborated more on the concept, flow, and process of mobile transaction platform development.